Michael O’Hanlon & Robert L. Welsch (eds.): Hunting the Gatherers. Ethnographic Collectors, Agents and Agency in Melanesia, 1870s-1930s - Liep, John (Tidsskriftet Antropologi, 2002)
Anmeldes af John Liep